Relativistic numerical hydrodynamics - Wilson, James R. (Cambridge University Press, 2003)
This book presents an overview of the computational framework in which calculations of relativistic hydrodynamics have been developed. It summarizes the jargon and methods used in the field, and provides illustrative applications to real physical systems. The authors explain how to break down the complexities of Einstein's equations and fluid dynamics, stressing the viability of the Euler–Lagrange approach to astrophysical problems. The book contains techniques and algorithms enabling one to build computer simulations of relativistic fluid problems for various astrophysical systems in one, two and three dimensions. It also shows the reader how to test relativistic hydrodynamics codes. Suitable for graduate courses on astrophysical hydrodynamics and relativistic astrophysics, this book also provides a valuable reference for researchers already working in the field
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Mathematisches Modell; Relativistic fluid dynamics / Mathematical models; Hydrodynamics / Mathematical models; Relativistische Hydrodynamik